1986
DOI: 10.1007/bf02082643
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic renal denervation in conscious restrained rats

Abstract: Sodium (Na), calcium (Ca), inorganic phosphate (Pi) and water excretion were measured in nondiuretic (ND) and extracellular fluid (ECF) volume expanded (VE) conscious restrained rats four weeks after denervation or sham-denervation of the left kidney. On the day of the study the animals were lightly anaesthetized with ether and the femoral vessels on one side were catheterized. Urine was collected from both kidneys. The animals were allowed to recover for 3 hours and studied in a restraining chamber. In ND ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although salt balance was not assessed in the present studies, cryodenervation of renal nerves may also have decreased arterial pressure by attenuating the increase in renal tubular sodium reabsorption reported with fructose feeding and high salt intake (20). Efferent renal sympathetic nerves impinge upon the renal tubular cells (5) and stimulate sodium transport (40,50). Fructose augments renal tubule sodium reabsorption by directly increasing the activity of proximal tubule sodiumhydrogen exchanger 3 and indirectly by sensitizing proximal tubule sodium transport to ANG II (9).…”
Section: Fructose-high Salt: Pra and Ang IImentioning
confidence: 92%
“…Although salt balance was not assessed in the present studies, cryodenervation of renal nerves may also have decreased arterial pressure by attenuating the increase in renal tubular sodium reabsorption reported with fructose feeding and high salt intake (20). Efferent renal sympathetic nerves impinge upon the renal tubular cells (5) and stimulate sodium transport (40,50). Fructose augments renal tubule sodium reabsorption by directly increasing the activity of proximal tubule sodiumhydrogen exchanger 3 and indirectly by sensitizing proximal tubule sodium transport to ANG II (9).…”
Section: Fructose-high Salt: Pra and Ang IImentioning
confidence: 92%
“…In fact, classic studies show that inhibition of adrenergic function by either pharmacological or surgical techniques increases salt and water excretion (5,14). Other studies have shown a natriuretic and diuretic response to chronic renal DnX (51,56), which we believe would be augmented in the HF state.…”
Section: Limitationsmentioning
confidence: 95%
“…Studies later in the 1970s and early 1980s involved the role of the renal nerves in determining sodium and water excretion [46][47][48], showing that the water diuresis in the denervated kidney was accompanied by decrease in sodium reabsorption without any detectable change in glomerular filtration rate (GFR), whilst renal nerve stimulation induced an increase in sodium reabsorption, again without any change in GFR.…”
Section: Carl Gottschalk: the Scientistmentioning
confidence: 99%